PENGARUH KEPATUHAN AUDITOR PADA KODE ETIK DAN ETIKA PROFESI TERHADAP KUALITAS AUDIT (Studi Empiris pada Kantor Akuntan Publik di DKI Jakarta) - Mayuri Ahda Valen; Sudarno Sudarno (Diponegoro Journal of Accounting, 2018)
The purpose of this study is to determine the impact of auditor’s compliance to integrity, independency, professional efficiency, professional conduct, and confidentiality of information as ethical code of auditing on audit quality. The study used primary data by sending questionnaires to auditors work at DKI Jakarta Public Accounting Firm which listed in Otoritas Jasa Keuangan. Out of 152 questionnaires distributed, 102 were collected and analyzed using multiple regression analysis with SPSS 22.0. The test results proved that auditor’s compliance to integrity, independency, professional efficiency, professional conduct, and confidentiality of information as the ethical rules of auditing had positively significant impact on audit quality. It means the higher auditor’s compliance to ethical rules of auditing, the greater the impact on the quality of audit.